THE INFLUENCE OF THE BOUNDEDNESS OF POLYNOMIAL POTENTIALS ON THE SPECTRUM OF THE SCHRODINGER-EQUATION - TASELI, H (Academic Press Inc Jnl-Comp Subscriptions, 1992)
[Abstract Not Available]
Keywords: Quantum-Mechanical Systems; Generalized Anharmonic-Oscillators; Hypervirial Analysis; Boundary-Conditions; Eigenvalue Problems